Corrosion performance of concrete using palm oil fuel ash (POFA) as a cement replacement material - Hanisah, Harun (2013)
With growing concern in the past decade over attributes to poor quality of concrete due to the durability especially in corrosion problem, various parameters and testing were suggested for improvement the quality of concrete composite. The development and use of blended cement is growing rapidly in the construction industry mainly due to considerations of cost saving, energy saving, environmental protection and conservation of resources. Demand for the high durability and environmental friendly nowadays developed POFA as an alternative material to replace cement in construction field. The use of POFA to replace a portion of cement has result significant saving in the cost of cement production. In this research, the durability towards chloride penetration in concrete was assessed. The influence of POFA on the corrosion performance of concrete was studied by some, accelerated short term technique in sodium chloride solutions. By adopting various activated techniques such as physical and chemical methods, hydration of POFA blended cement was accelerated and thereby improved the corrosion resistance of concrete. Concrete specimen prepared with 10%, 20% and 30% of POFA replacement were evaluated for their impressed voltage test, half cell potential test and chloride binding capacity test and the testing results were compared with those for OPC concrete without POFA. All the specimens were cured for 28 days before the testing was done. The study confirmed that level of 20% POFA replacement as cement improved the corrosion resistance properties. Therefore, POFA can be use as a cement replacement material to improve the corrosion resistance of concrete. At the same time, the problem of disposal of palm oil industry can be solved and new product can be produced to generate economic resources.